Applications of Quantitative Systems Pharmacology in Model‐Informed Drug Discovery: Perspective on Impact and Opportunities - Erica L. Bradshaw; Mary E. Spilker; Richard Zang; Loveleena Bansal; Handan He; Rhys D.O. Jones; Kha Le; Mark Penney; Edgar Schuck; Brian Topp; Alice Tsai; Christine Xu; et al. (Wiley, 2019)
Abstract Quantitative systems pharmacology (QSP) approaches have been increasingly applied in the pharmaceutical since the landmark white paper published in 2011 by a National Institutes of Health working group brought attention to the discipline. In this perspective, we discuss QSP in the context of other modeling approaches and highlight the impact of QSP across various stages of drug development and therapeutic areas. We discuss challenges to the field as well as future opportunities.